Allosteric regulation within the highly interconnected structural scaffold of AraC/XylS homologs tolerates a wide range of amino acid changes. Issue 1 (16th August 2021) - Picard, Hunter R.; Schwingen, Kristen S.; Green, Lisa M.; Shis, David L.; Egan, Susan M.; Bennett, Matthew R.; Swint‐Kruse, Liskin
Abstract: To create bacterial transcription "circuits" for biotechnology, one approach is to recombine natural transcription factors, promoters, and operators. Additional novel functions can be engineered from existing transcription factors such as the E. coli AraC transcriptional activator, for which binding to DNA is modulated by binding L‐arabinose. Here, we engineered chimeric AraC/XylS transcription activators that recognized ara DNA binding sites and responded to varied effector ligands. The first step, identifying domain boundaries in the natural homologs, was challenging because (i) no full‐length, dimeric structures were available and (ii) extremely low sequence identities (≤10%) among homologs precluded traditional assemblies of sequence alignments. Thus, to identify domains, we built and aligned structural models of the natural proteins. The designed chimeric activators were assessed for function, which was then further improved by random mutagenesis. Several mutational variants were identified for an XylSAraC chimera that responded to benzoate; two enhanced activation to near that of wild‐type AraC. For an RhaRAraC chimera, a variant with five additional substitutions enabled transcriptional activation in response to rhamnose. These five changes were dispersed across the protein structure, and combinatorial experiments testing subsets of substitutions showed significant non‐additivity. Combined, the structure modeling and epistasis suggest that the common AraC/XylS structural scaffold is highly interconnected, with complex intra‐protein and inter‐domain communication pathways enabling allosteric regulation. At the same time, the observed epistasis and the low sequence identities of the natural homologs suggest that the structural scaffold and function of transcriptional regulation are nevertheless highly accommodating of amino acid changes.